Diagnostic Accuracy of Magnetic Resonance Imaging in Diagnosing Malignant Musculoskeletal Tumours, Taking Histopathology as Gold Standard - Liaquat, Fatimah; Alia, Nayab; Ayub, Maham; Sikander, Mishal (Indus Journal of Bioscience Research, 2025)
Objective: The rationale of this study is to determine the capability of MRI in diagnosing malignant musculoskeletal tumours, by measuring the sensitivity and specificity of MRI for musculoskeletal tumours. Study design: Cross-sectional (validation) study. Settings: Department of Radiology Madinah Teaching Hospital, Faisalabad. Duration of study: 1st January 2024 to 30th June 2024. Methodology: The study comprised 120 patients aged 20 to 70 years presenting suspected musculoskeletal tumors of duration >4 weeks. Patients taking chemotherapy for any type of lesions, liver cirrhosis, undergone orthopedic surgery, claustrophobic patients and with cardiac pacemakers were excluded. Next, a 3.0 T MRI machine was used for magnetic resonance imaging. Axial and coronal T1WI and axial and sagittal fat-suppressed T2WI were among the traditional MRI procedures. The consultant radiologist assessed the MRI results for malignant musculoskeletal tumors (present or absent) based on the following criteria: big diameter (>6 cm), heterogeneous signal intensity on T1-weighted MRI, high signal intensity on T2-weighted MRI, and peritumoral edema. Following a biopsy, the histology report and the MRI results were compared for each patient. Results: MRI sensitivity was (93.85%), specificity (87.27%), PPV (89.71%), NPV (92.31%), and diagnostic accuracy (90.83%) in the diagnosis of malignant musculoskeletal tumours. Conclusion: According to the study’s findings, MRI is an extremely sensitive and precise imaging technique for diagnosis of malignant musculoskeletal tumours.